Food photography : from snapshots to great shots - Young, Nicole S. (Peachpit Press, 2011)
"In Food Photography: From Snapshots to Great Shots, photographer Nicole Young dishes up the basics on getting the right camera equipment--lights, lenses, reflectors, etc.--and takes you through the key photographic principles of aperture, ISO, and shutter speed. She then discusses lighting and composition and shows how to style food using props, fabrics, and tabletops. Finally, she explains how to improve your photos through sharpening, color enhancement, and other editing techniques. Beautifully illustrated with large, vibrant photos, this book offers the practical advice and expert shooting tips you need to get the food images you want every time you pick up your camera"--Back cover.